Практические вопросы применения систем технического зрения - Зубенко, Я. А. (My University, 2018)
Machine vision involves identifying the information that is contained in the image or visual scene for further processing. In the work, three existing methods for recognizing objects in an image are considered: contour analysis, pattern search and key point mapping.
Keywords: Техническое зрение; Робототехника; Контурный анализ